Increased pharmaceutical exports have both aggregate and distributional effects - Nikolaj Mose Dreisig Hansen; Mia Herløv Jørgensen (Danmarks Nationalbank, 2024)
We use the Disaggregated Economic Accounts (DEA) model, developed by Andersen et al. (2023), to study the consequences of an increase in Danish pharmaceuticals exports. The model predicts that consumption and output increase following an increase in pharmaceutical export, but that the increase in output is temporary and vanishes when wages adjust. Although aggregate output is unchanged in the longer run, activity shifts between municipalities and industries. We compare these effects to the effects of a similar increase in general manufacturing exports.
Keywords: 330; Pharmaceuticals; export; distributional effect; disaggregation; Denmark; Arzneimittel; Export; Verteilungswirkung; Disaggregation; Dänemark